Guiding and including vulnerable-driven populations : Process of Vocational Guidance in the Transgender Popular Mocha Cellis High School - Kanje, Nora Julia (2018)
The work presents a vocational guidance proposal that was carried out in the Transgender Popular “Mocha Cellis”, High School in 2014. The intention is to promote reflection on the transgender population in terms of social and educational inclusion, and contribute to give visibility to the difficulties they experience. The proposal invites counselors to reflect on their own choices; such as the way to think about transgender population; and to assume the design of ethical guiding approaches.